Comparative and evolutionary analyses of the divergence of plant oligosaccharyltransferase STT3 isoforms. Issue 3 (19th February 2020) - Niu, Guanting; Shao, Zhuqing; Liu, Chuanfa; Chen, Tianshu; Jiao, Qingsong; Hong, Zhi
Abstract : STT3 is a catalytic subunit of hetero‐oligomeric oligosaccharyltransferase (OST), which is important for asparagine‐linked glycosylation. In mammals and plants, OSTs with different STT3 isoforms exhibit distinct levels of enzymatic efficiency or different responses to stressors. Although two different STT3 isoforms have been identified in both plants and animals, it remains unclear whether these isoforms result from gene duplication in an ancestral eukaryote. Furthermore, the molecular mechanisms underlying the functional divergences between the two STT3 isoforms in plant have not been well elucidated. Here, we conducted phylogenetic analysis of the major evolutionary node species and suggested that gene duplications of STT3 may have occurred independently in animals and plants. Across land plants, the exon–intron structure differed between the two STT3 isoforms, but was highly conserved for each isoform. Most angiosperm STT3a genes had 23 exons with intron phase 0, while STT3b genes had 6 exons with intron phase 2. Characteristic motifs (motif 18 and 19) of STT3s were mapped to different structure domains in the plant STT3 proteins. These two motifs overlap with regions of high nonsynonymous‐to‐synonymous substitution rates, suggesting the regions may be related to functional difference between STT3a and STT3b. In addition, promoter elements and gene expression profiles were different between the two isoforms, indicating expression pattern divergence of the two genes. Collectively, the identified differences may result in the functional divergence of plant STT3s. Abstract : STT3 is a catalytic subunit of oligosaccharyltransferase (OST) which is important for N‐glycosylation. Two subtypes of STT3 exist in animal and plant through independent duplications. An ancient separation of STT3 in the common ancestor of plants was discovered. Different elements in the promoters, distinct motifs, and auxiliary subunits may confer divergent catalytic ability on OST containing STT3a or STT3b.